MOST COMMON BACTERIAL ENTEROPATHOGENS IN CHILDREN - V. Popescu (Amaltea Medical Publishing House, 2008)
This article focuses on the five most common bacterial enteropathogens of the developed world - Helicobacter pylori, Escherichia coli, Shigella, Salmonella and Campylobacter from the perspective of how they cause disease and how they relate to each other.